Strategi Guru Tahfidz dalam Meningkatkan Mutu Hafalan Al-Qur’an di Kelas IX Putra MTs Pondok Pesantren Modern Islam Assalaam - Aufa Faza Adzkiya (Jayapangus Press, 2026)
Tahfidz Al-Qur’an learning plays an important role in Islamic education, particularly in maintaining the quality of Qur’anic recitation and fostering students’ character development. Modern Islamic boarding schools face challenges related to dense academic activities that may affect the consistency and quality of students’ memorization, thereby requiring effective and sustainable tahfidz learning strategies. This study aims to describe the strategies employed by tahfidz teachers in improving the quality of Qur’an memorization among ninth-grade male students at MTs Pondok Pesantren Modern Islam Assalaam, as well as to identify supporting factors, inhibiting factors, and the evaluation system implemented. This research used a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman model, while data validity was ensured through source and method triangulation. The findings indicate that tahfidz teachers place mastery of tahsin as a fundamental prerequisite before memorization and consistently apply the talaqqi, tikrar, and muraja’ah methods. The tahfidz program is supported by a religious boarding school environment, strong collaboration among educators, and an intensive supervision system, although it still faces obstacles such as fluctuations in students’ motivation, limited time availability, and differences in Qur’anic reading abilities. In conclusion, improving the quality of Qur’an memorization can be achieved through structured learning strategies, tiered evaluation systems, and intensive mentoring oriented toward the accuracy of recitation and the development of students’ spiritual character.